Systematic design of a strain gauge calibration device for wayside measurement systems - Çelik, Abdullah; Metin, Muzaffer (Metrology and Measurement Systems, 2026)
Wayside measurements by means of a strain gauge placed on rails are an important test method to measure the wheel-rail contact forces that determine the safety of rail vehicles traveling on the track. In this method, to enhance the reliability of the monitoring results, strain gauge sections and measurement equipment should be calibrated under operating conditions. In this study, a design of a device has been developed for the calibration of strain gauges used in wayside measurement techniques. The systematic approach proposed by Pahl and Beitz and further developed by Feldhusen and Grote was utilised in the design process. With this innovative design, a safe, simple, compact, and user-friendly device capable of applying both vertical and horizontal forces with a single unit has been developed.